A Novel Technique for Experimental Flow Visualization of Mechanical Valves. Issue 2 (March 2016) - Huang Zhang, Pablo S.; Dalal, Alex R.; Kresh, J. Yasha; Laub, Glenn W.
Abstract : The geometry of the hinge region in mechanical heart valves has been postulated to play an important role in the development of thromboembolic events (TEs). This study describes a novel technique developed to visualize washout characteristics in mechanical valve hinge areas. A dairy-based colloidal suspension (DBCS) was used as a high-contrast tracer. It was introduced directly into the hinge-containing sections of two commercially available valves mounted in laser-milled fluidic channels and subsequently washed out at several flow rates. Time-lapse images were analyzed to determine the average washout rate and generate intensity topography maps of the DBCS clearance. As flow increased, washout improved and clearance times were shorter in all cases. Significantly different washout rate time constants were observed between valves, average >40% faster clearance ( p < 0.01). The topographic maps revealed that each valve had a characteristic pattern of washout. The technique proved reproducible with a maximum recorded standard error of mean (SEM) of ±3.9. Although the experimental washout dynamics have yet to be correlated with in vivo visualization studies, the methodology may help identify key flow features influencing TEs. This visualization methodology can be a useful tool to help evaluate stagnation zones in new and existing heart valve hinge designs. Abstract : Supplemental Digital Content is available in the text.